2019
DOI: 10.1002/cbic.201900050
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Route to Menaquinone towards Isochorismate‐Derived Metabolites

Abstract: Chorismate and isochorismate constitute branch‐point intermediates in the biosynthesis of many aromatic metabolites in microorganisms and plants. To obtain unnatural compounds, we modified the route to menaquinone in Escherichia coli . We propose a model for the binding of isochorismate to the active site of MenD ((1 R ,2 S , 5 S ,6 S )‐2‐succinyl‐5‐enolpyruvyl‐6‐hydroxycyclohex‐3‐ene‐1‐carboxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Identification of such as yet enigmatic enzymes might lead to the amino derivatives being recognised as important metabolic branching points contributing to a much larger biosynthetic diversity, as was proposed for the biosynthesis of stravidins (18), echinosporins (39), and SEPHCHC derivatives (36)(37)(38) prepared with variants of MenD. 32,39,140 In addition, the elucidation of the tundrenone (40) biosynthetic pathway suggests an undescribed C-C coupling reaction utilising chorismate as a substrate (Fig. 6).…”
Section: The Metabolic Flux Into the Different Branches Starting From (Iso)chorismate Is Directed By Allosteric Regulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Identification of such as yet enigmatic enzymes might lead to the amino derivatives being recognised as important metabolic branching points contributing to a much larger biosynthetic diversity, as was proposed for the biosynthesis of stravidins (18), echinosporins (39), and SEPHCHC derivatives (36)(37)(38) prepared with variants of MenD. 32,39,140 In addition, the elucidation of the tundrenone (40) biosynthetic pathway suggests an undescribed C-C coupling reaction utilising chorismate as a substrate (Fig. 6).…”
Section: The Metabolic Flux Into the Different Branches Starting From (Iso)chorismate Is Directed By Allosteric Regulationmentioning
confidence: 99%
“…5). 31,32,139 Moreover, Fries et al reported the preparative in vivo production of SEPHCHC, (iso)SDHCHC, and (iso)SAHCHC using engineered E. coli strains. Rationally designed MenD variants, based on a docking model with '1,6-dihydroisochorismate' as a surrogate intermediate, increased the yields of fermentations and in vitro reactions significantly (6-and 23-fold).…”
Section: The Metabolic Flux Into the Different Branches Starting From (Iso)chorismate Is Directed By Allosteric Regulationmentioning
confidence: 99%
See 3 more Smart Citations